Combination of lime stone and fly ash in the adsorption of iron (Fe) metal from coal acid mine drainage - Cici Wulandari; Shinta Indah; Vera Bachtiar (LPPMPK- Universitas Muhammadiyah Cileungsi, 2025)
Coal mining activities often produce acid mine drainage characterized by low pH values below 5 and high concentrations of heavy metals including iron (Fe). If the water is not managed properly, it can impact the environment due to the influence of acidity and high concentrations of dissolved metals. This research aims to utilize the combination of activated limestone and fly ash by heating at 110°C for 3 hours for acid mine drainage treatment, namely neutralizing pH and adsorbing heavy metal Fe. The selection of adsorbent materials was based on economic considerations, abundant availability, and utilization of fly ash waste. The method used was batch adsorption experiments with contact times of 30 and 60 minutes. Acid mine drainage from coal mine with initial pH 4.55 and Fe metal concentration 7.58 mg/L. The adsorbent combination of limestone and fly ash in the ratio of 1:1, 1:2, and 2:1. From the experimental results, it was obtained that the adsorbent combination was able to neutralize pH up to 6 and remove Fe up to 1.35 mg/L was the ratio of 1:2 with a stirring time of 30 minutes. So it can be concluded that adding fly ash dose 2 times compared to the dose of limestone is more effective to raise the pH value and remove Fe heavy metal, because the higher the dose given, the more ion adsorption sites will be available